Does the artery compression technique affect how much hematoma forms during a cardiac catheterization procedure? A systematic review of randomized controlled trials - Hani, Salam Bani; AlOsta, Mohammad R.; Othman, Elham H.; Alomari, Shahd E. (International Journal of Innovative Research and Scientific Studies, 2025)
It is standard practice to apply manual compression or mechanical devices to the puncture site after a cardiac catheterization to lessen the possibility of hematoma formation and bleeding. Hemostasis, or the cessation of bleeding, is the intended outcome. The purpose of this review is to ascertain whether using manual compression or other mechanical devices can lessen hematoma in patients following a cardiac catheterization procedure after removing the sheath. This systematic review was performed following PRISMA guidelines. A comprehensive search was carried out using multiple databases, including Science Direct, PubMed/MEDLINE, CINAHL, and Cochrane Library. A total of 52 studies were found in the selected databases. After eliminating 13 duplicates, 39 were screened for titles and abstracts. Twenty-two studies were selected for full-text screening, and 8 of them were eligible for the study criteria and included in the review. The studies that were chosen were all randomized controlled trials. After removing the catheter sheath, various interventions were attempted in the experiments to establish hemostasis. Patients who underwent radial catheterization were reported in three studies, while patients who underwent femoral catheterization were recorded in five studies. Multi-dimensional techniques could be utilized after sheath removal post-cardiac catheterization to promote hemostasis and reduce possible complications. However, the decision between manual compression and mechanical devices is influenced by several variables, including the patient’s health condition, the sheath’s size, and the access site (femoral or radial). Mechanical closure, in addition to manual compression techniques, can be more consistent and controlled, which may shorten the time needed for hemostasis.